Antifungal Activity of Essential Oils from Three Artemisia Species against Colletotrichum gloeosporioides of Mango - Xing Huang; Tiantian Liu; Chunxiang Zhou; Yulin Huang; Xing Liu; Haibin Yuan (MDPI AG, 2021)
Post-harvest diseases of mango reduce fruit quality and cause severe yield losses with completely unmarketable fruits. The most common diseases of mangos are anthracnose (Colletotrichum gloeosporioides). In this study, the antibacterial activities of essential oils from Artemisia scoparia, Artemisia lavandulaefolia, and Artemisia annua against C. gloeosporioides were tested. The results showed that the essential oil of A. scoparia was more effective by the agar diffusion method; the EC50 value was 9.32 µL/mL. The inhibition rate was 100%, at a concentration of 10 μL/mL, through the spore germination method. The morphological changes of the mycelium were observed by scanning electron microscopy (SEM), the mycelia treated with essential oils showed shrinking, deformity, fracture, and dryness through SEM. A. scoparia essential oil was inoculated in vivo and subjected to paroxysm testing under natural conditions. A. scoparia had significantly inhibitory activity, and the inhibition rate was 66.23% in vivo inoculation tests after 10 days. The inhibition rate was 92.06% in the paroxysm test under natural conditions after 15 days. Finally, A. acoparia essential oil was analyzed by gas chromatography-mass spectrometry. The main compounds were 2-ethenyl-Naphthalene (23.5%), 2,4-pentadiynyl-Benzene (11.8%), 1,2-dimethoxy-4-(2-propenyl)-Benzene (10.0%), β-Pinene (8.0%), and 1-methyl-4-(1-methylethyl)-1,4-Cyclohexadiene (6.3%). The results have revealed the potential use of A. scoparia essential oil against post-harvest fungal pathogens C. gloeosporioides.